Emerging Temperament Perspectives on Heterogeneity and Psychopathology Risk - Sarah L. Karalunas; Erica D. Musser; Koraly Pérez-Edgar (Clinical Psychological Science, 2026)
In this special issue, we bring together a set of studies that collectively demonstrate the power of temperament-based frameworks for advancing understanding of the structure of psychopathology and its underlying mechanisms, particularly in domains marked by substantial heterogeneity, comorbidity, early emergence, and developmental change. A temperament-based approach was chosen as the focus to help link multiple levels of analysis, capture both transdiagnostic and disorder-specific risk, and facilitate a life-span approach to understanding the mechanisms and structure of psychopathology. The contributions to this special issue move the field forward by integrating dimensional and categorical conceptualizations of psychopathology, linking complex influences on risk within a biopsychosocial framework, and bridging understanding from very early development through emerging adulthood. Each contribution highlights the continuing importance of developmental psychopathology principles and perspectives. Together, the findings point to key next directions for the field, including linking sometimes disparate child and adult research traditions, incorporating multiple timescales of study simultaneously, and continuing to tackle questions of generalizability in partnership with the communities that the research is meant to serve.